(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The use of idiomatic phraseology in professional communication is an essential aspect of effective business discourse. Business idioms, commonly used in negotiations, emails, presentations, and meetings, enhance fluency, create rapport, and convey complex ideas succinctly. This article explores the impact of business idioms on workplace interactions, analyzing their role in facilitating clear communication, strengthening professional relationships, and influencing decisionmaking. Additionally, it examines challenges non-native speakers face in interpreting and using business idioms accurately, particularly in cross-cultural contexts. By highlighting real-world examples and case studies, the study aims to provide insights into how idiomatic expressions shape corporate communication and contribute to business success.